STRATEGI PEMBELAJARAN BAHASA INDONESIA BERBASIS AI DALAM MENINGKATKAN LITERASI DIGITAL SISWA - Anita Candra Dewi (Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the effectiveness of artificial intelligence (AI)-based learning strategies in improving students' digital literacy in Indonesian language subjects. With the rapid development of digital technology, the utilization of AI is expected to help students in understanding, evaluating, and improving their language skills. This study used a quantitative method with a quasi-experimental approach, involving 40 junior high school students in Makassar City as research subjects. Data were collected through pre-test, post-test, questionnaire, and interview, then analyzed using t-test to measure significant changes. The results showed that AI-based learning had a positive impact on improving students' digital literacy, indicated by a significant increase in post-test scores compared to pre-test. As many as 85% of students felt the benefits of the auto-correction and instant feedback features that helped in understanding and correcting language errors. However, limited access to technology and the readiness of educators are challenges in implementing this method. Therefore, infrastructure improvement and training for teachers are needed so that AI-based learning strategies can be implemented more optimally and inclusively.